Strategi Komunikasi Stakeholder dalam Pengembangan Wisata Berbasis Alam dan Budaya di Pantai Kuta Mandalika Provinsi Nusa Tenggara Barat - Sami’un, Sami’un; Supratman, Supratman (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
Landscape development for ecotourism potential is one of the focuses of the National Development Planning Agency through the Indonesian Biodiversity Strategy and Action Plan program. Currently, the tourism sector has the potential to contribute to the country's foreign exchange, like other ASEAN countries, where the tourism sector has contributed more than 10% of the country's foreign exchange. In Indonesia, the contribution of the tourism sector is still below 10%. Bali Province has become a favorite tourist destination, both for domestic and foreign tourists. However, along with the progress of modernity, the capacity of the Province of Bali has become very vulnerable, so that the development of tourism on the island of Bali can be directed to the island of Lombok, West Nusa Tenggara Province. One of the potential areas to be developed is the Mandalika Special Economic Zone (SEZ), which is not too far from Zainuddin Abdul Majid International Airport (ZAMIA), making Mandalika have easy access for tourists. The development of new ecotourism areas requires scientific studies to identify the potential and social conditions of the local community. This study aims to explore the tourism potential based on the nature and culture of the people of Kuta Mandalika, as well as develop development and marketing strategies.